Impact of Lactococcus lactis as starter culture on microbiota and metabolome profile of an Italian raw milk cheese. (November 2020) - Dolci, Paola; Ferrocino, Ilario; Giordano, Manuela; Pramotton, Rita; Vernetti-Prot, Luca; Zenato, Simona; Barmaz, Andrea
Abstract: The standardisation of raw milk cheeses without losing their typicality is an ambitious goal. In the present study, the performance of two Lactococcus lactis autochthonous starter cultures (AS1 and AS2) was evaluated for the production of Valle d'Aosta (VdA, Italy) Fromadzo PDO, in terms of competition and persistence capacity (by rep-PCR strain characterisation), influence on indigenous microbial population (by metataxonomic approach) and volatilome development (by GC–MS and sensory analysis). The best performance was shown by AS2 starter mixture, which was able to colonise Fromadzo cheeses at the expense of indigenous lactic microbiota, and reached mean frequency values of 87% and 70% in 30 day-ripened products from valley floor and alpine pasture milk, respectively. Moreover, both kinds of cheeses, obtained using AS2, achieved the best scores in terms of aroma and taste, the pasture cheese also achieving the best score for texture.